ANALISIS FAKTOR KEBIJAKAN HUTANG PERUSAHAAN MANUFAKTUR - Tossy Aryanto; Wachidah Fauziyanti; Siti Rochmah (JURNAL STIE SEMARANG, 2021)
The use of debt by the company must also be controlled, so that it does not exceed the company's own capital, so that internal control is needed, such as management and intensive supervision from the majority shareholder, namely institutional parties. The population in this study is a case study of manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2018 period. This study uses secondary data. Collection in the form of annual financial reports of manufacturing companies listed on the Indonesia Stock Exchange via the IDX web. The method of analysis was carried out using descriptive statistical tests, classical assumption tests and multiple regression analysis. The results of the analysis that has been carried out on companies in the manufacturing sector, regarding the influence of company size, profitability, sales growth on debt policy, it can be concluded that company size has a significant effect on debt policy. Profitability has a significant effect on debt policy and sales growth has no significant effect on debt policy. Advice to potential investors and investors, to pay more attention to these variables in the company before making investment decisions. Management needs to further improve the effectiveness and efficiency of the company such as minimizing costs properly which can increase company profits and ultimately increase company value.